2020
DOI: 10.1038/s41467-020-15533-0
|View full text |Cite
|
Sign up to set email alerts
|

Representation of visual uncertainty through neural gain variability

Abstract: Uncertainty is intrinsic to perception. Neural circuits which process sensory information must therefore also represent the reliability of this information. How they do so is a topic of debate. We propose a model of visual cortex in which average neural response strength encodes stimulus features, while cross-neuron variability in response gain encodes the uncertainty of these features. To test this model, we studied spiking activity of neurons in macaque V1 and V2 elicited by repeated presentations of stimuli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(101 citation statements)
references
References 56 publications
11
90
0
Order By: Relevance
“…To control for sensory confounds and isolate specific effects of perceptual uncertainty, it should be possible to design stimulus protocols where the perceptual task is always performed with an identical probe stimulus, but where perceptual uncertainty was manipulated by prior exposure to different priming stimuli. These predictions echo recent findings that link neural gain variability to perceptual uncertainty induced by manipulations of low-level image statistics [36]. This link between uncertainty and variability is also qualitatively captured by our model (see Supplemental Fig.…”
Section: New Predictions Of Adaptive Codingsupporting
confidence: 91%
“…To control for sensory confounds and isolate specific effects of perceptual uncertainty, it should be possible to design stimulus protocols where the perceptual task is always performed with an identical probe stimulus, but where perceptual uncertainty was manipulated by prior exposure to different priming stimuli. These predictions echo recent findings that link neural gain variability to perceptual uncertainty induced by manipulations of low-level image statistics [36]. This link between uncertainty and variability is also qualitatively captured by our model (see Supplemental Fig.…”
Section: New Predictions Of Adaptive Codingsupporting
confidence: 91%
“…Other work has established the connection between normalization and variability more directly. A descriptive model of stochastic normalization has been shown to fit changes in variability with stimulus contrast (Coen-Cagli and Solomon 2019) and orientation noise (Henaff, Boundy-Singer, et al 2020), and revealed that, even for fixed stimuli, variability is reduced during epochs of strong normalization (Coen-Cagli and Solomon 2019). Our analytical results on normalization and variability bridge the gap between this literature and a theory of the computational role of variability.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent model (Henaff, Boundy-Singer, et al 2020) proposes that uncertainty is represented in the response variability, and is thus related to sampling and to our work. However, they propose that variability is partitioned into two terms, Poisson variability and fluctuations in response gain (Goris, Movshon, et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slow systematic changes may occur in this dataset analyzed here, but they operate at a time scale that makes them orthogonal to our theory. In particular, slow multiplicative, low-dimensional noise may serve other functional roles, such as encoding uncertainty in visual areas [26; 27], but it cannot serve as a labeling mechanism of the type proposed here. Such variability would convey information about informativeness on a time scale slower than that needed for single trial feedback and decoder learning.…”
Section: Discussionmentioning
confidence: 99%